Behavioural pre-testing of COVID Tracker, Ireland's contact-tracing app - Hannah Julienne; Ciarán Lavin; Cameron A. Belton; Martina Barjaková; Shane Timmons; Pete Lunn (The Economic and Social Research Institute (ESRI), 2020)
Contact-tracing mobile phone apps have the potential to play a role in controlling the spread of COVID-19, but their success hinges on widespread uptake by the public. We report a study that behaviourally pre-tested COVID Tracker, Ireland's contact-tracing app, prior to its launch with a large sample of smartphone users. The study was funded by the Department of Health and run in co-operation with the app's developers, NearForm. Participants were randomised to receive different versions of a trial app. They responded to an online survey while downloading and using the app on their phones in real time. The experimental manipulations focused on three broad areas: (i) the level of privacy assurance provided in the app, (ii) the goal-framing of the purpose of the app and (iii) the structuring of the exposure notification received by users if they are recorded as a close contact. Almost one in five participants mentioned privacy concerns in relation to their likelihood of downloading the app. Including additional assurances regarding the privacy of users' data in the app successfully lowered participants' privacy concerns and boosted engagement. This finding fed into the final version of the app released in July 2020. We also found minor beneficial effects of restructuring the exposure notification, but did not find any significant differences between two different types of goal-framing, other than a subtle effect on how the exposure notification is interpreted. Overall, our results demonstrate the value of pre-testing contact-tracing apps from a behavioural perspective to boost uptake, trust and participation.
Keywords: 330